Application of boron doped diamond electrode for voltammetric monitoring of quality of phytostimulation preparations - Usenko, Alona; Chýlková, Jaromíra; Váňa, Jiří; Janíková, Lenka; Šelešovská, Renáta (BEST Servis, 2021)
The aim of the present paper was to examine voltammetric behavior of plant stimulators employing boron doped diamond electrode. A triazine paclobutrazol, which was selected as a representative, provided one well-developed signal in an alkaline electrolytes at about +2000 mV, which could be detected owing to a wide potential window of BDDE. Simple and rapid voltammetric method was developed and it was reached low limit of quantification (LOQ = 0.15 μg mL−1) and detection as well (LOD = 0.05 μg mL−1). The applicability of the proposed method was verified by voltammetric analysis of phytostimulation preparation containing paclobutrazol and difenoconazol.
Využití borem dopované diamantové elektrody při voltametrické analýze kvality Využití borem dopované diamantové elektrody při voltametrické analýze kvality přípravků ovlivňujících růst rostlin
Keywords: phytostimulator; paclobutrazol; difenoconazol; indole-3-acetic acid; indole-3-butyric acid; 1-Naphthaleneacetic acid; voltammetry; boron doped diamond electrode; fytostimulátor; paclobutrazol; difenoconazol; kyselina indol-3-octová; kyselina indol-3-máselná; kyselina 1-naftalenoctová; voltametrie; borem dopovaná diamantová elektroda